BUREAUCRATIC ANALYSIS OF INDONESIA’S MINISTRY OF DEFENCE: ADVANCING NATIONAL DEFENSE DIPLOMACY THROUGH THE 2024 INDONESIA-AUSTRALIA DEFENCE COOPERATION AGREEMENT (DCA) - Haura, Shafa; Angelica Maria D. C; Jamalia Sumala; Salma Indri Yulianti; Muhammad Prakoso Aji (Mandala: Jurnal Ilmu Hubungan Internasional, 2025)
This study analyzes the bureaucratic system of Indonesia’s Ministry of Defence in implementing the 2024 Indonesia-Australia Defence Cooperation Agreement (DCA). Literature review and interviews identified key challenges cross-national coordination complexity, legal/linguistic differences, and shared funding mechanisms. Ditkersinhan’s America-Pacific Subdirectorate served as the primary coordinator. Collaboration with Indonesia’s Foreign Ministry and the Australian Defence Attaché ensured administrative-operational alignment. Kemhan’s bureaucratic system proved effective, supported by hierarchical simplification and digitalization enhancing responsiveness. Tangible DCA outcomes included joint exercises and military education exchanges. The study concludes that bureaucratic efficiency through collaborative governance and procedural reform is critical for successful defense diplomacy, enabling systemic adaptation and strengthened regional stability.